Adaptation pathways: A review of approaches and a learning framework. Issue 116 (February 2021) - Werners, Saskia E.; Wise, Russell M.; Butler, James R.A.; Totin, Edmond; Vincent, Katharine
Highlights: Adaptation pathways have become recognised as sequences of actions, which can be implemented progressively, depending on future dynamics Pathways can be alternatives towards a defined objective or broad directions of change for different strategic outcomes Pathways approaches orientate around performance-thresholds, multiple-stakeholders or transformation Pathways are developed to meet adaptation needs, promote collaborative learning and /or enable transformations Reflexive learning is needed on pathways approaches to realise their potential in different decision contexts. Abstract: Adaptation pathways have experienced growing popularity as a decision-focussed approach in climate adaptation research and planning. Despite the increasing and broadening use of adaptation pathways reported in the literature, there has not yet been a systematic attempt to review, compare and contrast approaches to adaptation pathways design and their application. In this paper we address this gap through a literature review of conceptual and applied studies of adaptation pathways in the context of climate change. Adaptation pathways started to be conceptualised in 2010. They have become recognised as sequences of actions, which can be implemented progressively, depending on how the future unfolds and the development of knowledge. A difference between scholars is whether pathways are understood as alternative sequences of measures to realise a well-defined adaptation objective, or as broad directions of change for different strategic aims or outcomes. Analysis of case studies on adaptation pathways development showed three clusters of approaches: (a) performance-threshold oriented, (b) multi-stakeholder oriented, and (c) transformation oriented approaches. These broadly correspond to three desired outcomes of pathways development: (i) meeting short and long-term adaptation needs, (ii) promoting collaborative learning, adaptive planning and adaptive capacity, (iii) accounting for complexity and long-term change, including a potential need for transformation. Yet, as of now there is little evidence of the utility of different approaches for pathways development in different decision contexts. Scholars appear to be guided more by how they understand the adaptation problem and by what approaches are known to them, than by the context of the case. Attention is needed on who defines objectives and outcomes for pathway development. Based on the review, we present a learning framework to guide systematic reflection about why and how adaptation pathways are developed. Lessons learned by application of the framework will enable refinement of pathways approaches to make full use of the potential in different decision contexts.